Targeting ADCC: A different approach to HER2 breast cancer in the immunotherapy era - Mandó, Pablo (2021)
The clinical outcome of patients with human epidermal growth factor receptor 2 (HER2) amplified breast carcinoma (BC) has improved with the development of anti-HER2 targeted therapies. However, patients can experience disease recurrence after curative intent and disease progression in the metastatic setting. In the current era of evolving immunotherapy agents, the understanding of the immune response against HER2 tumor cells developed by anti-HER2 antibodies (Abs) is rapidly evolving. Trastuzumab therapy promotes Natural Killer (NK) cell activation in patients with BC overexpressing HER2, indicating that the efficacy of short-term trastuzumab monotherapy, albeit direct inhibition of HER, could also be related with antibody-dependent cell-mediated cytotoxicity (ADCC). Currently, dual HER2 blockade using trastuzumab and pertuzumab is the standard of care in early and advanced disease as this combination could confer an additive effect in ADCC. In patients with disease relapse or progression, ADCC may be hampered by several factors such as FcγRIIIa polymorphism and an immunosuppressive environment, among others. Hence, new drug development strategies are being investigated aiming to boost the ADCC response triggered by anti-HER2 therapy. In this review, we summarize these strategies and the rationale, through mAbs engineering and combinatorial strategies, focusing on clinical results and ongoing trials.